The application of precast concrete technology in industrialised building system (IBS) [compact disc] - 461394 Siti Mazlinah Abdul Rahim (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2005